Four versus six cycles of CHOP chemotherapy in combination with six applications of rituximab in patients with aggressive B-cell lymphoma with favourable prognosis (FLYER): a randomised, phase 3, non-inferiority trial - Pöschel, Viola; Held, Gerhard Wolfgang; Ziepert, Marita; Witzens-Harig, Mathias; Holte, Harald; Thurner, Lorenz; Borchmann, Peter; Viardot, Andreas; Sökler, Martin; Keller, Ulrich; Schmidt, Christian; Truemper, Lorenz; et al. (The lancet, 2019)
Background - Six cycles of R-CHOP (rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone) are the standard treatment for aggressive B-cell non-Hodgkin lymphoma. In the FLYER trial, we assessed whether four cycles of CHOP plus six applications of rituximab are non-inferior to six cycles of R-CHOP in a population of patients with B-cell non-Hodgkin lymphoma with favourable prognosis. - Methods - This two-arm, open-label, international, multicentre, prospective, randomised phase 3 non-inferiority trial was done at 138 clinical sites in Denmark, Israel, Italy, Norway, and Germany. We enrolled patients aged 18-60 years, with stage I-II disease, normal serum lactate dehydrogenase concentration, ECOG performance status 0-1, and without bulky disease (maximal tumour diameter <7·5 cm). Randomisation was computer-based and done centrally in a 1:1 ratio using the Pocock minimisation algorithm after stratification for centres, stage (I vs II), and extralymphatic sites (no vs yes). Patients were assigned to receive either six cycles of R-CHOP or four cycles of R-CHOP plus two doses of rituximab. CHOP comprised cyclophosphamide (750 mg/m2), doxorubicin (50 mg/m2), and vincristine (1·4 mg/m2, with a maximum total dose of 2 mg), all administered intravenously on day 1, plus oral prednisone or prednisolone at the discretion of the investigator (100 mg) administered on days 1-5. Rituximab was given at a dose of 375 mg/m2 of body surface area. Cycles were repeated every 21 days. No radiotherapy was planned except for testicular lymphoma treatment. The primary endpoint was progression-free survival after 3 years. The primary analysis was done in the intention-to-treat population. Safety was assessed in all patients who received at least one dose of assigned treatment. A non-inferiority margin of −5·5% was chosen. The trial, which is completed, was prospectively registered at ClinicalTrials.gov, NCT00278421. - Findings - Between Dec 2, 2005, and Oct 7, 2016, 592 patients were enrolled, of whom 295 patients were randomly assigned to receive six cycles of R-CHOP and 297 were assigned to receive four cycles of R-CHOP plus two doses of rituximab. Four patients in the four-cycles group withdrew informed consent before the start of treatment, so 588 patients were included in the intention-to-treat analysis. After a median follow-up of 66 months (IQR 42-100), 3-year progression-free survival of patients who had four cycles of R-CHOP plus two doses of rituximab was 96% (95% CI 94-99), which was 3% better (lower limit of the one-sided 95% CI for the difference was 0%) than six cycles of R-CHOP, demonstrating the non-inferiority of the four-cycles regimen. 294 haematological and 1036 non-haematological adverse events were documented in the four-cycles group compared with 426 haematological and 1280 non-haematological adverse events in the six-cycles group. Two patients, both in the six-cycles group, died during study therapy. - Interpretation - In young patients with aggressive B-cell non-Hodgkin lymphoma and favourable prognosis, four cycles of R-CHOP is non-inferior to six cycles of R-CHOP, with relevant reduction of toxic effects. Thus, chemotherapy can be reduced without compromising outcomes in this population. - Funding - Deutsche Krebshilfe.